Genomic imbalances in peripheral blood confirm the diagnosis of myelodysplastic syndrome in a patient presenting with non-immune hemolytic anemia. (2016) - Zahid, Mohammad Faizan; Khan, Nadia; Pei, Jianming; Testa, Joseph R.; Dulaimi, Essel
Abstract: Myelodysplastic syndrome (MDS) is a clonal stem-cell disorder characterized by dyshematopoiesis. We report a patient who presented with cytopenias and microangiopathic hemolytic anemia. Chromosome microarray analysis (CMA), using single nucleotide polymorphism arrays, on peripheral blood revealed genomic imbalances indicative of MDS, which was confirmed by bone marrow examination. This report highlights the importance of suspecting MDS in patients with cytopenias and microangiopathic hemolytic anemia. CMA of peripheral blood may assist in the preliminary diagnosis of MDS, representing a comparatively less invasive diagnostic procedure and may aid bone marrow evaluation when an aspirate sample is insufficient for conventional cytogenetic analysis. Highlights: Myelodysplastic syndromes (MDS) may manifest as non-immune hemolytic anemia. Schistocytosis may be evident on peripheral blood smear in a subset of MDS patients. Utilization of peripheral blood DNA to detect genomic imbalances and mutations. Genomic imbalances detection by chromosomal microarray analysis (CMA). CMA of peripheral blood may complement diagnostics in MDS.